Nutritional deficiencies in endurance runners with Chron's Disease - Palmer, Mary (My University, 2012)
The purpose of this study was to examine the dietary intake of endurance runners with Crohn's disease so that exact dietary deficiencies may be identified, specifically related to: vitamins A, D, E, K, fiber, iron, and total caloric intake
Color poster with text, charts, and image
Keywords: Running--Diet therapy.; Athletes--Nutritional aspects; Crohn's disease--Nutritional aspects; Crohn's disease--Diet therapy; Posters